Advances in catalytic hydrogen combustion research: Catalysts, mechanism, kinetics, and reactor designs. (18th November 2021) - Kim, Jongho; Yu, Jianglong; Lee, Soonho; Tahmasebi, Arash; Jeon, Chung-Hwan; Lucas, John
Abstract: Compared with conventional hydrogen-air combustion, catalytic hydrogen combustion (CHC) exhibits higher safety and efficiency and ultra-low NOx emissions. Significant advances in CHC have been achieved in recent years through fundamental research. Therefore, the state-of-the-art CHC technology is comprehensively reviewed herein, including catalyst development, catalytic reactors, and the factors impacting the kinetics of various CHC systems. Furthermore, the progress made in CHC catalyst design over the years is examined, and detailed information regarding their synthesis, structure, and characteristics are presented. The comparison of several types of CHC reactors, including fixed-bed, monolithic, and microchannel reactors, is presented in terms of their operational features and performances. The effects of several operating parameters, including the reaction temperature, hydrogen-to-oxygen stoichiometric ratio, space velocity, residence time, and operating pressure, of the CHC processes are reviewed. The catalytic reaction pathways and the kinetics of the CHC processes are also summarized, advancing the understanding of the underlying chemistry on the catalyst surfaces. This review analyzes the various catalysts, reactor types, operating factors, and underlying mechanisms involved in CHC to better understand the mass transfer, heat transfer, and chemistry during this process. Finally, future research directions are proposed to explore the design of catalytic reactors for CHC. Highlights: Advances in catalytic combustion of hydrogen are reviewed. Catalytic hydrogen combustion is a promising technology for mitigating NOx emissions. Bimetallic catalysts exhibit superior performance than monometallic catalysts. Kinetic studies revealed reaction pathways occurring on the catalyst surface. Microchannel reactors provide several advantages for catalytic combustion.